PENYULUHAN NILAI-NILAI KOEKSISTENSI DALAM QUR’AN DAN SUNNAH KEPADA MASYARAKAT DI BANGLADESH - Nirwana AN, Andri; Mahmudulhassan; Tiffany Lovely; Saif Uddin Ahmed Khondoker; Fahmi Dolles Marshal (Yayasan Baitul Hikmah al-Zain, 2024)
Historically, Bangladesh has been host to numerous religious minorities, such as Buddhists, Hindus, Sheiks, Animists, and Atheists. It made a significant contribution to the continuation of social, political, and religious concord among people of many religious views after the liberation war. In varied communities like Bangladesh, religious concord is especially dependent on religious cooperation. This study used a mixed-method approach to investigate the dynamics of religious cohabitation in Bangladesh, depending on Islamic texts, particularly the Quran and Hadith, to provide background. In this study, the concepts and ideals that facilitate peaceful coexistence among various religious groups in Bangladesh are examined through an analysis of pertinent passages and teachings. The study also evaluates Bangladesh's current state of minority groups’ social, political, and religious rights. The study’s conclusions add to the conversation on religious coexistence and provide useful advice for promoting interfaith harmony and understanding in Bangladesh and elsewhere. The outcome demonstrates that Islam places a strong emphasis on treating minorities and individuals of all religions with respect and decency. Bangladesh is a multicultural country that is suitable for coexisting peacefully with individuals of different backgrounds. Regardless of caste or religion, people here are kind and considerate of one another. At times conflicts are seen between Muslims and non-Muslims as people think most of them are personal and political provocations.